MINORITAS MILITAN: SIKAP KOMUNITAS MATIUS TERHADAP ROH KAPITALISME - Demianus Nataniel (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2017)
Capitalism has evolved since the time of Matthew’s own community. Capitalism development was mainly cultivated by the Romans who controlled Antioch as the context of Matthew’s own community. The author outlines how communities Matthew emphasizes Jesus’ teaching against the adverse effects of Capitalism, like greed to accumulate wealth for themselves without ever attentive to the needs of the poor and oppressed. Community Matthew pushed ideal vision of Jesus that regard the life of this world by structuring society full of peace and prosperity.